Changes in physico-chemical and volatile aroma compound composition of Gewürztraminer wine as a result of late and ice harvest. (1st April 2016) - Lukić, Igor; Radeka, Sanja; Grozaj, Nikola; Staver, Mario; Peršurić, Đordano
Highlights: Changes in aroma of Gewürztraminer wine after late and ice harvest were studied. Late harvest wine had higher amounts of the majority of aromas than control. Icewine had complex aroma (terpenes, furans, acetals, etc.) and reduced esters. Main odorants in ice wine: cis -rose oxide, β-damascenone, 1, 1-diethoxyethane. Ice wine had increased terpenic, floral, pungent and ripe fruit aroma series. Abstract: To investigate the changes in physico-chemical and aroma composition after late and ice harvest, Gewürztraminer wines were subjected to standard, enzymatic and GC/MS analysis. Late harvest (LHGW) and ice wines (IHGW) contained more sugars, extract and volatile acidity than standard wines (SGW). IHGW had elevated glycerol and gluconic acid amounts. LHGW was richer in monoterpenol oxides, β-damascenone, 1-octen-3-ol, acetates, ethyl cinnamate and 4-vinylguaiacol than SGW. IHGW contained even higher amounts, with increased citronellol, acetaldehyde, ethyl acetate, dicarboxylic acids esters, benzenoids, furans and acetals, and reduced fermentation aroma compounds. Based on odour activity values, the strongest odorants in SGW were fruity esters. In LHGW the impact of esters increased, while in IHGW cis -rose oxide, β-damascenone and 1, 1-diethoxyethane emerged as the most potent. Fruity and sweet were the dominant aroma compound series in SGW and LHGW, but in IHGW declined, while terpenic, floral, chemical, pungent and ripe fruit aroma compound series increased.